Rancang Bangun Sistem Pengarsipan Data Aturan Pedoman dan SOP Berbasis Web Dengan Menggunakan Metode Index Field (Studi Kasus : Universitas Catur Insan Cendekia) - Melly Amalia; Lena Magdalena; Tiara Eka Putri (Institut Pendidikan Indonesia, 2020)
Archives have an important role in an agency or company to support administrative processes or activities carried out in the company. If the records are not well managed, it will be difficult to find the information that has been stored so that it can hinder further work processes. Therefore archives should be managed using a good and correct management system. The IT study program at the Catur Insan Cendekia Cirebon University does not yet have a filing system for data on rules, guidelines and SOP, so currently a system is needed that can help performance related to data archiving of rules, guidelines and SOP. In this study the authors implemented data archiving rules, guidelines and web-based SOP using the index field method to make it easier to search for data and maintain document security and was carried out using a codeigniter framework, using MYSQL as database management which is popularly used to build web applications that source. and data management using a database. The result of this data archiving system for rules, guidelines and SOP is that data retrieval does not need to take a lot of time and effort so that the required data can be accessed quickly and easily. So that data can be applied automatically based on the category so that data archiving is more effective and efficient.Keywords : Data Rules, Filing System, Guidelines, Index Field, Standar Operasional Prosedur, SOP.